The Making of Pakistani Human Bombs - Khuram Iqbal (Lanham Lexington Books, 2015)
Based on interviews with failed suicide bombers, officials of Pakistani law enforcement agencies involved in interrogating high-profile self-immolation attacks, and content analysis of Jihadi publications produced in local languages, this book offers the first empirically grounded analysis of suicide terrorism in Pakistan.
Include Index, Bibliography and Appendix
Keywords: Suicide bombers -- Suicide bombings -- Pakistan